The ever‐increasing necessity of mass spectrometry in dissecting protein post‐translational modifications catalyzed by bacterial effectors - Jin, Jie; Yuan, Yi; Xian, Wei; Tang, Zhiheng; Fu, Jiaqi; Liu, Xiaoyun (Molecular microbiology, 2023)
Protein post‐translational modifications (PTMs), such as ADP‐ribosylation and phosphorylation, regulate multiple fundamental biological processes in cells. During bacterial infection, effector proteins are delivered into host cells through dedicated bacterial secretion systems and can modulate important cellular pathways by covalently modifying their host targets. These strategies enable intruding bacteria to subvert various host processes, thereby promoting their own survival and proliferation. Despite rapid expansion of our understanding of effector‐mediated PTMs in host cells, analytical measurements of these molecular events still pose significant challenges in the study of host–pathogen interactions. Nevertheless, with major technical breakthroughs in the last two decades, mass spectrometry (MS) has evolved to be a valuable tool for detecting protein PTMs and mapping modification sites. Additionally, large‐scale PTM profiling, facilitated by different enrichment strategies prior to MS analysis, allows high‐throughput screening of host enzymatic substrates of bacterial effectors. In this review, we summarize the advances in the studies of two representative PTMs (i.e., ADP‐ribosylation and phosphorylation) catalyzed by bacterial effectors during infection. Importantly, we will discuss the ever‐increasing role of MS in understanding these molecular events and how the latest MS‐based tools can aid in future studies of this booming area of pathogenic bacteria–host interactions. Some recent work on protein ADP‐ribosylation (and related ADP‐riboxanation) and classical phosphorylation are highlighted in the mini review as examples to illustrate our current understanding of this fascinating area in host–pathogen interactions. This review will focus on the application of MS‐based approaches in the study of host protein modifications catalyzed by bacterial effectors.